E-Government Innovation Model in Improving the Quality of Public Administration Service in Deli Serdang Regency - Sitompul, Bella Viona; Handayani, Sri; Sibuea, Jeff Denver; Exaudi; Hura, Rizen Chariswan Grace; Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
The development of information technology has encouraged local governments to undertake digital transformation in public service delivery. E-Government has emerged as an innovative strategy to improve the quality of public administrative services, ensuring they are effective, efficient, transparent, and accountable. This study is a conceptual research aimed at analyzing E-Government innovation models in enhancing the quality of public administrative services in Deli Serdang Regency. The research method employed is a literature study with a conceptual approach to E-Government theory, public service innovation, information system quality, and digital government policy. The results of the study indicate that the implementation of E-Government in Deli Serdang Regency contributes to the acceleration of administrative processes, improvement of bureaucratic work efficiency, and enhancement of service quality for the community. Nevertheless, E-Government implementation still faces challenges such as limited human resources, digital literacy, and system integration. Therefore, strengthening apparatus capacity and developing integrated systems are crucial factors in supporting the success of E-Government innovation in Deli Serdang Regency.